Anaerobic decolorization of an azo dye by a mixed culture - Gonçalves, I. C. (2001)
Wool dyeing wastewater contains xenobiotic compounds that can be removed by biotechnological processes. Studies on various dyes showed that anaerobic processes are suitable to alter azo dyes as a first step of the biodegradation process. These compounds are reduced by anaerobic consortia to aromatic amines and its ultimate degradation can be achieved by a further aerobic treatment. Studies on degradation rate of an wool acid dye were performed in batch systems inoculated with anaerobic biomass. A commercial diazo dye, Acid Red 73, was added to the synthetic medium in which glucose was used as sole carbon source. Results indicated that the Acid Red 73 was partially degraded by a mixed culture of anaerobic bacteria and a decolorization of 90% was obtained. Kinetics studies on removal of the colour showed that the decolorization rate was several times faster than the degradation rate of glucose for a range of dye concentrations between 60 mg/L and 400 mg/L. A first order kinetic model was used for dye concentrations up to 200 mg/L. For higher concentrations a model similar to the Michaelis-Menten equation was better fitted to the experimental data.